Volume 2: Pipeline Integrity Management 2012
DOI: 10.1115/ipc2012-90427
|View full text |Cite
|
Sign up to set email alerts
|

Full Scale Cyclic Fatigue Testing of Dented Pipelines and Development of a Validated Dented Pipe Finite Element Model

Abstract: Dents in buried pipelines can occur due to a number of potential causes; the pipe resting on rock, third party machinery strike, rock strikes during backfilling, amongst others. The long-term integrity of a dented pipeline segment is a complex function of a variety of parameters, including pipe geometry, indenter shape, dent depth, indenter support, pressure history at and following indentation. In order to estimate the safe remaining operational life of a dented pipeline, all of these factors must be accounte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
6
2
Order By: Relevance
“…9, there also exists discrepancy in the predicted residual dent depth between the current study and the investigations conducted by Tiku et al (2012). The reasons for a much higher elastic rebound observed in the study by Tiku et al (2012) are unclear but it is stated the FE model had scatter that lay outside the ± 10 % range. elastic rebound after removal of the indenter for an unconstrained dent with no internal pressure, was 70 mm in the present study and ~50 mm in the Tiku et al (2012) investigation.…”
Section: Fig 8: Comparison Of the Load-deflection Response Between Tcontrasting
confidence: 76%
See 3 more Smart Citations
“…9, there also exists discrepancy in the predicted residual dent depth between the current study and the investigations conducted by Tiku et al (2012). The reasons for a much higher elastic rebound observed in the study by Tiku et al (2012) are unclear but it is stated the FE model had scatter that lay outside the ± 10 % range. elastic rebound after removal of the indenter for an unconstrained dent with no internal pressure, was 70 mm in the present study and ~50 mm in the Tiku et al (2012) investigation.…”
Section: Fig 8: Comparison Of the Load-deflection Response Between Tcontrasting
confidence: 76%
“…9, there also exists discrepancy in the predicted residual dent depth between the current study and the investigations conducted by Tiku et al (2012). 9, there also exists discrepancy in the predicted residual dent depth between the current study and the investigations conducted by Tiku et al (2012).…”
Section: Fig 8: Comparison Of the Load-deflection Response Between Tcontrasting
confidence: 51%
See 2 more Smart Citations
“…Recent studies on constrained (impinged by a hard object) and unconstrained (free to flex) pipe segments have attempted to model fatigue fracture in pipes [29]. Fatigue studies on dented pipes have been shown to develop colonies of parallel cracks that visually appear to be SCC, but are only fatigue.…”
Section: Analysis and Discussionmentioning
confidence: 99%